Geology - Foster, Robert J. (C.E. Merrill Pub. Co., 1985)
his indispensable guide to the fundamentals of geology is the ideal way to introduce yourself to all the basics, from rocks, minerals, and fossil fuels to earthquakes, volcanoes, and plate tectonics. Using quick quizzes and self-tests to reinforce key concepts, Geology carefully walks you through billions of years of Earth history